PENGEMBANGAN PERANGKAT PEMBELAJARAN PROGRAM LINEAR BERBASIS MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN SCIENTIFIC DENGAN MEDIA E-LEARNING PADA SISWA KELAS X MULTIMEDIA SMK NEGERI 1 SOMBA OPU KABUPATEN GOWA - Sirwanti, Sirwanti (MaPan : Jurnal Matematika dan Pembelajaran, 2016)
The study aimed at discovering the process and the result of development of learning tools of linear program with cooperative learning model based of scientific approach using e-learning media wich is valid, practical, and effective in grade X Multimedia at SMKN 1 Somba Opu. The study is a development research. Data were collected using observation sheet, test, and questionnaire of student’s response. The subjects of the study were grade X Multimedia students at SMKN 1 Somba Opu. The learning tools developed consisted of student’s book, student’s worksheet, lesson plan. The development process of learning tools used modification instrument from Thiagarajan (4-D) wich consisted of defining phase, design phase, development phase, and dissemination phase. The results of study revealed that (i) the learning tools were valid because the result of validation was in the interval 3,5 ≤ < 4,5 Overall, the mean of = 4.1 meaning that the validated component was in the category of valid and could be used with small revision, (ii) the learning tools was practical already because it obtained the category of implemented on the application of learning activity, and (iii) the learning tools were affective already because it fulfilled three indicators off effectiveness, namely (1) the achievement of learning result, (2) student’s activity, (3) student’s response included in the criteria and expected indicators.